The hidden spear: A case series on elongated styloid process - Agrawal, Dr.Aryan; PAREEK, Dr. AVIKA; CHAUDHARY, Dr.TANISHKA; MEENA, DR.MANOJ; BAGHLA, Dr.PALLAVI; Kaswan, Shobhit; SINGH, Dr.KANISHKA (Indian Journal of Case Reports, 2026)
The styloid process (SP) is a slender, pointed projection of the temporal bone at the base of the skull, typically 20–30 mm long. It serves as a crucial anchor for muscles and ligaments involving the tongue and larynx. When its length exceeds 30 mm or when the stylohyoid ligament becomes calcified, it is termed an elongated SP. In some cases, this condition is associated with Eagle syndrome. Eagle’s syndrome refers to unilateral or bilateral elongation of the SP or calcified stylohyoid ligament, along with other symptoms, such as dysphagia, otalgia, tinnitus, and globus pharyngeus. Many individuals with an elongated SP do not show any symptoms, and the condition is often discovered incidentally on radiographs. Early diagnosis is important to prevent confusion with other causes of orofacial pain and to provide appropriate treatment. Awareness among dental practitioners, especially in oral medicine and radiology, is essential for the proper identification and management of this condition. The present case series report covers cases of elongation of the SP as incidental findings, discussing clinical and radiographic features along with a brief review of the literature.